Determining the Frequency of Depression and Cognitive Dysfunction in Patients with Multiple Sclerosis - Bilgi, Emine; Ozdemir, Hasan Huseyin; Bulut, Serpil (Turkish Neurological Soc, 2013)
Objective: Multiple sclerosis (MS) not only leads to different levels of disabilities in mobility and functional activities, but also creates severe disability and impairs the quality of life by limiting the patient's social and occupational life. Most MS patients experience depression. In addition, cognitive dysfunction is also present. In this study we aimed to determine the frequency of depression and cognitive dysfunction in MS patients. Material and Method: One hundred and eight patients diagnosed with MS were evaluated. was by using Brief Repeatable Battery of Neuropsychological Test (10/36 Spatial Recall Test, Symbol Digit Modalities Test, Paced Auditory Serial Test, Word List Generation Test), Beck Depression Inventory and Benedict Test. Results: Of the 108 MS subjects who participated in the study, 69.4% (n=75) were female, while 30.6% (n=33) were male. Depression was detected in 19.5% (n=21) of the patients, and cognitive dysfunction was found in 41.7% (n=45). Depression and cognitive dysfunction were detected simultaneously in 13.9% (n=15) of the patients. Discussion: Depression and cognitive dysfunction are not rare in patients with MS. A multidisciplinary approach is needed to treat the patients diagnosed with MS.
Multipl sklerozlu hastalarda depresyon ve kognitif fonksiyon bozuklu?u sikli?inin belirlenmesi
Keywords: Multiple sclerosis; cognitive dysfunction; depression; frequency